If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 8x + 23 Reorder the terms: 9 = 23 + 8x Solving 9 = 23 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 9 + -8x = 23 + 8x + -8x Combine like terms: 8x + -8x = 0 9 + -8x = 23 + 0 9 + -8x = 23 Add '-9' to each side of the equation. 9 + -9 + -8x = 23 + -9 Combine like terms: 9 + -9 = 0 0 + -8x = 23 + -9 -8x = 23 + -9 Combine like terms: 23 + -9 = 14 -8x = 14 Divide each side by '-8'. x = -1.75 Simplifying x = -1.75
| 10y/40=5 | | (x/2)+(1/5)=17 | | 5=x/7 | | 3x-24/3+4=13 | | 45+x+68+x+83=180 | | 3n^2-2n-40=0 | | 1/3b-1=5/6 | | x+2(1/2)=6(3/4) | | -3+p=-25 | | -2(4-3X)+9X-4= | | 7/12+y=1/6 | | 6(z-8)=7z-1 | | 2x/5=11 | | 153+-34=x | | -24=-28+z | | 297+-9=x | | 6x+2x=7x+6 | | 70+11x+11x=180 | | n-16/5 | | -4+z=-20 | | 90+x+58+x+38=180 | | r=sb | | t+25=10 | | 112+-7=x | | r+4.1=4.4 | | 3(4x+7)-4(X-2)=3(X+4)-2 | | (3x)/2-(12-x)/5=(7x+1)/3 | | -14=t+16 | | 1/3z=-11 | | 3x+12/6 | | 630+-90=x | | 48+-40=x |